The Assessment and Relationship Between Quality of Life and Physical Activity Levels in Greek Breast Cancer Female Patients under Chemotherapy - Maria Maridaki; Argyro Papadopetraki; Helen Karagianni; Michael Koutsilieris; Anastassios Philippou (MDPI AG, 2020)
A growing body of evidence suggests that physical activity (PA) can be a complementary intervention during breast cancer (BCa) treatment, contributing to the alleviation of the chemotherapy-related side-effects. The purpose of this study was to assess physical activity (PA) levels and quality of life (QoL) parameters of BCa patients undergoing chemotherapy and compare them with healthy controls. A total of 94 BCa female patients and 65 healthy women were recruited and self-reported QoL and PA levels. The results reveal that women suffering from BCa spent only 134 ± 469 metabolic equivalents (MET)/week in vigorous PAs compared with the healthy females who spent 985±1508 MET/week. Also, BCa patients were spending 4.62±2.58 h/day sitting, contrary to the 2.34±1.05 h/day of the controls. QoL was scored as 63.43±20.63 and 70.14±19.49 while physical functioning (PF) as 71.48±23.35 and 84.46±15.48 by BCa patients and healthy participants, respectively. Negative correlations were found between QoL and fatigue, PF and pain, and fatigue and dyspnea, while a positive correlation was found between QoL and PF. This study indicated that the BCa group accumulated many hours seated and refrained from vigorous Pas, preferring PAs of moderate intensity. Additionally, BCa patients’ levels of functioning and QoL were moderate to high; however, they were compromised by pain, dyspnea and fatigue.